Comparative cardiovascular benefits of individual SGLT2 inhibitors in type 2 diabetes and heart failure: a systematic review and network meta-analysis of randomized controlled trials - Kongmalai, Tanawan; Hadnorntun, Phorntida; Leelahavarong, Pattara; Kongmalai, Pinkawas; Srinonprasert, Varalak; Chirakarnjanakorn, Srisakul; Chaikledkaew, Usa; McKay, Gareth; Attia, John; Thakkinstian, Ammarin (Frontiers in Endocrinology, 2023)
Background: In patients with type 2 diabetes (T2D) and a history of heart failure (HF), sodiumglucose cotransporter-2 inhibitors (SGLT2i) have demonstrated cardiovascular (CV) benefits. However, the comparative efficacy of individual SGLT2i remains uncertain. This network metaanalysis examined the effectiveness and safety of five SGLT2i (canagliflozin, dapagliflozin, empagliflozin, ertugliflozin, sotagliflozin) on CV outcomes in these patients.Materials and Methods: PubMed, Embase and Cochrane central Registry of Controlled Trials were searched up to September 23, 2022, to identify all randomized controlled trials (RCTs) comparing SGLT2i to placebo in T2D patients with HF. Main outcomes included composite CV-death/heart failure hospitalization (HFH), HFH, CV death, all-cause mortality and adverse events. Pairwise and network meta-analysis approaches were applied.Results: Our analysis included 11 RCTs with a total of 20,438 patients with T2D and HF. All SGLT2i significantly reduced HFH compared to standard care (SoC) alone. "Add-on" SGLT2i, except ertugliflozin, significantly reduced composite CV-death/HFH relative to SoC alone. Moreover, canagliflozin had lower composite CV-death/HFH compared to dapagliflozin. Based on surface under the cumulative ranking curve (SUCRA), the top ranked SGLT2i for reducing HFH were canagliflozin (95.5%), sotagliflozin (66.0%) and empagliflozin (57.2%). Head-to-head comparisons found no significant differences between individual SGLT2i in reducing CV death. "Add-on" SGLT2i reduced all-cause mortality compared with SoC alone, although only dapagliflozin was statistically significant. No SGLT2i were significantly associated with serious adverse events. A sensitivity analysis focusing on HF-specific trials, dapagliflozin, empagliflozin, and sotagliflozin significantly reduced composite CV-death/HFH, consistent with the main analysis. However, no significant differences were identified from their head-to-head comparisons in the NMA. SUCRA indicated sotagliflozin with the highest probability of reducing composite CV-death/HFH (97.6%), followed by empagliflozin (58.4%) and dapagliflozin (44.0%).SGLT2is significantly reduce the composite CV-death/HFH outcome. Among them, canagliflozin may be considered the preferred treatment for patients with diabetes and a history of heart failure, but it may also be associated with an increased risk of any adverse events compared to other SGLT2i. However, a sensitivity analysis focusing on HF-specific trials identified sotagliflozin as the most likely agent to reduce CV-death/HFH, followed by empagliflozin and dapagliflozin.Review Registration: https://www.crd.york.ac.uk/prospero/, identifier CRD42022353754.